2D graphene-based advanced nanoarchitectonics for electrochemical biosensors: Applications in cancer biomarker detection - Mukherjee, Soumajit; Mukherjee, Atripan; Bytešníková, Zuzana; Ashrafi, Amirmansoor; Richtera, Lukáš; Adam, Vojtěch (ELSEVIER ADVANCED TECHNOLOGY, 2024)
Low-cost, rapid, and easy-to-use biosensors for various cancer biomarkers are of utmost importance in detecting cancer biomarkers for early-stage metastasis control and efficient diagnosis. The molecular complexity of cancer biomarkers is overwhelming, thus, the repeatability and reproducibility of measurements by biosensors are critical factors. Electrochemical biosensors are attractive alternatives in cancer diagnosis due to their low cost, simple operation, and promising analytical figures of merit. Recently graphene-derived nanostructures have been used extensively for the fabrication of electrochemical biosensors because of their unique physicochemical properties, including the high electrical conductivity, adsorption capacity, low cost and ease of mass production, presence of oxygen-containing functional groups that facilitate the bioreceptor immobilization, increased flexibility and mechanical strength, low cellular toxicity. Indeed, these properties make them advantageous compared to other alternatives. However, some drawbacks must be overcome to extend their use, such as poor and uncontrollable deposition on the substrate due to the low dispersity of some graphene materials and irreproducibility of the results because of the differences in various batches of the produced graphene materials. This review has documented the most recently developed strategies for electrochemical sensor fabrication. It differs in the categorization method compared to published works to draw greater attention to the wide opportunities of graphene nanomaterials for biological applications. Limitations and future scopes are discussed to advance the integration of novel technologies such as artificial intelligence, the internet of medical things, and triboelectric nanogenerators to eventually increase efficacy and efficiency.

Low-cost, rapid, and easy-to-use biosensors for various cancer biomarkers are of utmost importance in detecting cancer biomarkers for early-stage metastasis control and efficient diagnosis. The molecular complexity of cancer biomarkers is overwhelming, thus, the repeatability and reproducibility of measurements by biosensors are critical factors. Electrochemical biosensors are attractive alternatives in cancer diagnosis due to their low cost, simple operation, and promising analytical figures of merit. Recently graphene-derived nanostructures have been used extensively for the fabrication of electrochemical biosensors because of their unique physicochemical properties, including the high electrical conductivity, adsorption capacity, low cost and ease of mass production, presence of oxygen-containing functional groups that facilitate the bioreceptor immobilization, increased flexibility and mechanical strength, low cellular toxicity. Indeed, these properties make them advantageous compared to other alternatives. However, some drawbacks must be overcome to extend their use, such as poor and uncontrollable deposition on the substrate due to the low dispersity of some graphene materials and irreproducibility of the results because of the differences in various batches of the produced graphene materials. This review has documented the most recently developed strategies for electrochemical sensor fabrication. It differs in the categorization method compared to published works to draw greater attention to the wide opportunities of graphene nanomaterials for biological applications. Limitations and future scopes are discussed to advance the integration of novel technologies such as artificial intelligence, the internet of medical things, and triboelectric nanogenerators to eventually increase efficacy and efficiency.
2D graphene-based advanced nanoarchitectonics for electrochemical biosensors: Applications in cancer biomarker detection
Keywords: 2D nanocomposites; Sensor development; Electrochemical biosensor; Cancer biomarker; Graphene; 2D nanocomposites; Sensor development; Electrochemical biosensor; Cancer biomarker; Graphene